2021
DOI: 10.1007/s44007-021-00005-8
|View full text |Cite
|
Sign up to set email alerts
|

Even Values of Ramanujan’s Tau-Function

Abstract: In the spirit of Lehmer's speculation that Ramanujan's tau-function never vanishes, it is natural to ask whether any given integer α is a value of τ (n). For odd α, Murty, Murty, and Shorey proved that τ (n) = α for sufficiently large n. Several recent papers have identified explicit examples of odd α which are not tau-values. Here we apply these results (most notably the recent work of Bennett, Gherga, Patel, and Siksek) to offer the first examples of even integers that are not tau-values. Namely, for primes … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Shortly thereafter, Bennett, Gherga, Patel, and Siksek [5] proved that the same is true for any positive power of ℓ, and that τ (n) = ±3 a 5 b 7 c 11 d for any a, b, c, d ∈ Z ≥0 and any n > 1. Using some of these results concerning odd primes, Balakrishnan, Ono, and Tsai [4] were able to make progress eliminating even integers as values of the τ -function. For odd primes ℓ, they showed that…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Shortly thereafter, Bennett, Gherga, Patel, and Siksek [5] proved that the same is true for any positive power of ℓ, and that τ (n) = ±3 a 5 b 7 c 11 d for any a, b, c, d ∈ Z ≥0 and any n > 1. Using some of these results concerning odd primes, Balakrishnan, Ono, and Tsai [4] were able to make progress eliminating even integers as values of the τ -function. For odd primes ℓ, they showed that…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 99%
“…The proof of Theorem 1.1 follows the approach of [3] and [4] for odd and even values, respectively. For each α, we use the fact that smaller values have been excluded as values of the τ -function to show that τ (n) = α implies n = p a for some prime p. Due to the classification of primitive divisors of Lucas sequences in [6,1], we are able to restrict the list of possibilities for a, each of which we then eliminate using the congruences for the τ -function listed in [19].…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation